2022
DOI: 10.1093/jee/toac029
|View full text |Cite
|
Sign up to set email alerts
|

Hanseniaspora uvarum Attracts Drosophila suzukii (Diptera: Drosophilidae) With High Specificity

Abstract: Since the early phase of the intercontinental dispersal of Drosophila suzukii (Matsumura) (Diptera: Drosophilidae), fermentation baits have been used for monitoring. Self-made lures and commercial products are often based on wine and vinegar. From an ecological perspective, the formulation of these baits is expected to target especially vinegar flies associated with overripe fruit, such as Drosophila melanogaster (Meigen) (Diptera: Drosophilidae). Hanseniaspora uvarum (Niehaus) (Ascomycota: Saccharomyceta) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…4). Interestingly, parallel experiments conducted with headspaces of Hanseniaspora uvarum that were already available in our labs and on use for different projects (Mori et al 2017;Kleman et al 2022) revealed activation of DsuzOR69a subunits in proximity of compounds released at different retention times (Fig. 5, Online Resource 5).…”
Section: Gc-ssr Analysis Of Active Ligands and Headspace Collectionsmentioning
confidence: 88%
“…4). Interestingly, parallel experiments conducted with headspaces of Hanseniaspora uvarum that were already available in our labs and on use for different projects (Mori et al 2017;Kleman et al 2022) revealed activation of DsuzOR69a subunits in proximity of compounds released at different retention times (Fig. 5, Online Resource 5).…”
Section: Gc-ssr Analysis Of Active Ligands and Headspace Collectionsmentioning
confidence: 88%
“…Hanseniaspora uvarum can also be employed in another type of biological control to fight Drosophila suzukii, which already causes fruit harvest losses in Southern Europe, especially of grapes and cherries [15]. The strong attraction of the fruit flies to H. uvarum, presumably due to the efficient production of ester compounds like ethyl acetate, is thus employed to build traps for efficient pest management [16,17]. Interestingly, but not yet applied in oenology or medicine, H. uvarum also produces a killer toxin with activity against Candida species [18].…”
Section: Introductionmentioning
confidence: 99%